In Situ Carbon Homogeneous Doping on Ultrathin Bismuth Molybdate: A Dual‐Purpose Strategy for Efficient Molecular Oxygen Activation - Wang, Shengyao; Ding, Xing; Zhang, Xuehao; Pang, Hong; Hai, Xiao; Zhan, Guangming; Zhou, Wei; Song, Hui; Zhang, Lizhi; Chen, Hao; Ye, Jinhua (Advanced Functional Materials, 2017)
Solar‐driven activation of molecular oxygen, which harnesses light to produce reactive oxygen species for the removal of pollutants, is the most green and low‐cost approach for environmental remediation. The energy coupling between photons, excitons, and oxygen is the crucial step in this reaction and still remains a challenge. In this study, a dual‐purpose strategy for enhanced molecular oxygen activation is established by in situ carbon homogeneous doping on ultrathin Bi2MoO6 nanosheets for the first time. The C‐doped ultrathin 2D material exhibits an enlarged bandgap straddling the electrochemical potential of O2 /•O2− and H2O /•OH, without any attenuation of light absorption. An internal electric field and shortened carrier‐transportation distance are also found in the longitude orientation of the nanosheets ([001] axis), leading to a higher density of effective photogenerated carriers localized on the exposed {001} surface. As applied for the nitric oxide removal, the reactive rate over the ultrathin C‐doped Bi2MoO6 nanosheets is 4.3 times higher than that over the bulk counterparts as a result of the increasing reactive oxygen species. This new proof‐of‐concept strategy not only realizes the band structure engineering and charge transportation regulation but also paves a new way to construct highly efficient photocatalytic materials. A dual‐purpose strategy for enhanced molecular oxygen activation is established by in situ carbon homogeneous doping on ultrathin Bi2MoO6 nanosheets. The constructed material with shorter distance in the direction of charge transfer and promoted redox ability without losing any absorption of solar light is 4.3 times higher than that over the bulk counterparts in long‐term nitric oxide removal.